1963
DOI: 10.1139/v63-322
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Study of Xanthate and Dixanthogen Solutions

Abstract: Xanthate solutions of pH 6-10, prepared from "aged" potassium ethyl xanthate crystals, KEtX, were investigated spectrophotometrically in the region 190-400 mp and showed coexistence of xanthate ions, EtX-, dixanthogen, (EtX)z, and carbon disulphide, CS2. Optical density measurements on the spectra of dixanthogen solutions led to the evaluation of: molar absorptivities of dixanthogen a t wavelengths corresponding to the two main bands in the xanthate ion spectrum, i.e. a t 301 mP-6130 liter/mole cm, and a t 226… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(19 citation statements)
references
References 3 publications
0
18
0
1
Order By: Relevance
“…Xanthate oxidation, reaction (IV), had been considered irreversible and dixanthogen unreactive. However, spectrophotometric studies on dixanthogen dispersions by Pomianowski and Leja (1963) showed that dixanthogen does react in alkaline solutions and reverts partly to xanthate and decomposes to CS2 (see studies by Tipman (1970) and Figures 5.5b and 5.7). Patel (1960, 1961) established that aqueous oxidation of xanthate ion to dixanthogen is catalyzed by multivalent reducible ions such as Cu2+ and Fe 3 +.…”
Section: Hydrolysis Of the Xanthate Ionmentioning
confidence: 99%
“…Xanthate oxidation, reaction (IV), had been considered irreversible and dixanthogen unreactive. However, spectrophotometric studies on dixanthogen dispersions by Pomianowski and Leja (1963) showed that dixanthogen does react in alkaline solutions and reverts partly to xanthate and decomposes to CS2 (see studies by Tipman (1970) and Figures 5.5b and 5.7). Patel (1960, 1961) established that aqueous oxidation of xanthate ion to dixanthogen is catalyzed by multivalent reducible ions such as Cu2+ and Fe 3 +.…”
Section: Hydrolysis Of the Xanthate Ionmentioning
confidence: 99%
“…These increases are higher in the presence of L. ferrooxidans than in A. ferrooxidans tests (except in the presence of KIBX and KIPX) (Figure 1c,d). The instability of these collectors when pH < 3 could be an explanation for these increases, where the pH may increase as a result of the H + consumption from the solution for the decomposition of the collectors in the early stage of experiments (Equations (1) and (2)) [7,[22][23][24]. During the next 14 days, the ∆ pH decreased in all experiments.…”
Section: Subsectionmentioning
confidence: 93%
“…During the measurement, until day 21, DO 2 values remain lower than the DO 2 value of the control test (−∆ DO 2 ) for A. ferrooxidans tests except for NaEX and KAX, which show the highest positive deviations (Figure 3a,b). The presence of unstable collectors in the low pH culture can limit the availability (i.e., transfer) of oxygen (xanthates are unstable in acidic solutions, and their instabilities increase by decreasing the pH [7,[22][23][24]). These reactions' inhibitory effect increase the DO 2 value [36][37][38].…”
Section: Do 2 Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Woods et al (1995) showed that diethyldixanthogen does not form on pure gold surfaces below +300 mV SHE. It is believed that oxygen in the pulp helps in xanthate adsorption (Woods, 1976) and oxidation to dixanthogen (Finkelstein, 1967), whilst at high concentration it inhibits xanthate adsorption because of metal hydroxide formation at the mineral surface (Pomianowski and Leja, 1963). That is, increasing oxygen content increases the Eh, which enhances xanthate interaction with the mineral surface (Kuopanportti et al, 1997(Kuopanportti et al, , 2000.…”
Section: Collector Adsorption On Free Goldmentioning
confidence: 99%